Hubungan Antara Gaya Kepemimpinan dan Motivasi Kerja Dengan Prestasi Kerja Pegawai Dinas Pendidikan Pemuda dan Olahraga Kabupaten Tulang Bawang - MALIK Malik (e-JKPP, 2015)
With the Link title of Among Leadership Style And Motivate The Job [of] With The Labour Capacity of Officer On Duty Education of Young Fellow And Athletics of Regency of Tulang Bawang.Problem of this research is : (1) What Leadership Style of Among relating to Labour capacity of officer at On duty Education of Young fellow and Athletics of Regency of Tulang Bawang, (2) What Motivation relate to the Labour capacity of officer at On duty Education of Young fellow and Athletics of Regency of Tulang Bawang, ( 3) What Leadership Style and Motivate to relate to the make-up of Labour capacity of officer at On duty Education of Young fellow and Athletics of Regency of Konawe NorthResearch Method used in this research is Eksplanatory survey the. Research population as much 50 officer people at On duty Education of Young fellow and Athletics of Regency of Konawe North. While sampel that is as much 50 total or sampel people. Research variable [is] Leadership Style as free variable (X1) and Motivate Officer as free variable (X2) and also the make-up of labour capacity officer is variable trussed (Y)Result of research indicate that there is good link signifikan of leadership style and also motivate the officer with the labour capacity of officer at On duty Education of Young fellow and Athletics of Regency of Tulang Bawang, biggest link from variable of pembentuk of leadership style is dimension telling, while smallest dimension from variable of pembentuk of leadership style is dimension selling. While biggest dimension of its influence variable Motivate the officer that is motivate the eksternal and smallest that is internal motivation. Pursuant to research result, can be opened by that if leadership style and motivate the good job hence will be happened by the make-up of labour capacity at On duty Education of Young fellow and Athletics of Regency of Konawe North.